THE USING OF ANAGRAM TECHNIQUE TO IMPROVE STUDENTS’ VOCABULARY MASTERY (A RESEARCH CONDUCTED AT ELEVENTH GRADE STUDENTS OF SCIENCE CLASS A IN SMA NEGERI 1 PAGUYAMAN) - Hengki Bilaleya; Sartin T. Miolo; Sri Rumiyatiningsih Luwiti (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2023)
The purpose of this study is to determine whether or not the use of anagram technique can improve the students' English vocabulary mastery in science class A SMA Negeri 1 Paguyaman eleventh-grade students. This study used a pre-experimental design with one group pre-test and post-test, with the difference between the pre-test and post-test score indicating the effects of treatments. The data sample consisted of eleventh grade students from Science class A at SMA Negeri 1 Paguyaman. Twenty-five students were chosen as the sample by the researcher. The data was collected by the researcher using an instrument test that included a pre- and post-test. The T-test is being used to analyze the data in this study. The pre-test mean score of the students is (45.6). By the end of the study, the students' mean score is (75.2). The t-test result tcount 2.747 was higher than ttable 1.711. The outcome indicates that the alternative hypothesis (Ha) has been accepted and the null hypothesis (Ho) has been rejected. As a result, it is possible to conclude that the anagram technique can help students improve their vocabulary mastery.